Design, installation and calibration of a block of lysimeters to adjust the crop coefficient - León, Juan; Parra, Vicente; Peña, Robinson; Silva, Juan; Román, Daniel; Salazar, Francisco (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The efficient management of water resources using techniques that improve it uses, based on knowledge of evapotranspiration are key elements for crop production. Amongst main techniques for water management, the use of drainage lysimeter installed in the field below vegetable fields may be used to quantify the amount of water needed. The aim of this work is to design, install and calibrate a set of lysimeters for adjusting crop coefficient (Kc). In the calibration of the lysimeters, it was obtained that to induce drainage in lysimeters from one to five, an over-irrigation of 25% of the field capacity was needed, while the rest needed 50%. With lysimeters built the physical characteristic of soil could be simulated in this study.